1998
DOI: 10.1046/j.1471-4159.1998.71062574.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxin‐Induced Neuronal Death Is Associated with Response of a Unique Intracellular Aspartic Proteinase, Cathepsin E

Abstract: Excitotoxicity produced by excessive stimulation of glutamate receptors is known to lead to neuronal lesion and death. Here, we demonstrate that quantitative and qualitative changes in cathepsin E (CE) gene products are associated with execution of the excitotoxic neuronal death. Intracerebroventricular injection of kainate (KA) resulted in marked elevation of both mRNA and protein levels of CE in the rat hippocampal CA3 region, where the enzyme was mainly found in vulnerable neurons and activated microglia. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Thus, establishing the molecular pathways associated with the seizure-induced neuronal death may provide novel treatment strategies for patients with TLE. Although enhanced levels/expression of lysosomal enzymes does not always correlate with the degeneration of neurons, there is evidence that administration of kainic acid can lead to up-regulation of lysosomal enzymes in the affected regions of the brain (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012). This finding is substantiated, in part, by our study which shows an increase in the expression, levels and activity of cathepsins B and D in the hippocampus of kainic acid-treated rats compared to controls.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, establishing the molecular pathways associated with the seizure-induced neuronal death may provide novel treatment strategies for patients with TLE. Although enhanced levels/expression of lysosomal enzymes does not always correlate with the degeneration of neurons, there is evidence that administration of kainic acid can lead to up-regulation of lysosomal enzymes in the affected regions of the brain (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012). This finding is substantiated, in part, by our study which shows an increase in the expression, levels and activity of cathepsins B and D in the hippocampus of kainic acid-treated rats compared to controls.…”
Section: Discussionsupporting
confidence: 62%
“…These results suggest that cathepsins may have a role not only in normal cellular functioning but also in a variety of disorders associated with the degeneration of neurons, including TLE. Although some earlier studies have reported altered levels and/or activity of cathepsins in kainic acidinduced seizures (Hetman et al, 1995;Tominaga et al, 1998;Akahoshi et al, 2007;Ni et al, 2012), very little is known about the subcellular levels of the enzymes and their association, if any, to the degeneration of neurons. To address this issue, we measured the time-dependent alterations in the distribution, activity and cellular/subcellular levels of cathepsins B and D in the hippocampus of adult rats following systemic administration of kainic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin F, L, and S, which are involved in invariant chain degradation and peptide loading, are differently distributed among APCs. Cathepsin S is present in B cells, DCs, and m, whereas cathepsin F is more selectively expressed in tissue m. Neonatal microglial cells have been reported to express cathepsin S and L, but not F (13), while resting microglial cells have been reported to express cathepsin E (36). Global gene expression analysis confirms these observations.…”
Section: Proteasesmentioning
confidence: 68%
“…Various lysosomal proteases and their potential contribution to propagation of apoptosis are discussed (reviewed in [107]). Kazuyoshi Tominaga's data [108] indicated that excitotoxin-induced neuronal death was associated with a response of lysosome enzyme: cathepsin E. Our studies showed that lysosomal enzyme cathepsin B was involved in KA-induced excitotoxicity in rat striatum [22].…”
Section: Lysosomesmentioning
confidence: 91%